Ozone and Temperature May Hinder Adaptive Capacity of Mediterranean Perennial Grasses to Future Global Change Scenarios - Prieto-Benítez, Samuel; Ruiz-Checa, Raquel; González-Fernández, Ignacio; Elvira, Susana; Rucandio, Isabel; Alonso, Rocío; Bermejo-Bermejo, Victoria (MDPI, 2023)
Climate warming is recognized as a factor that threatens plant species in Mediterranean mountains. Tropospheric ozone (O3) should also be considered as another relevant stress factor for these ecosystems since current levels chronically exceed thresholds for plant protection in these areas. The main aim of the present study was to study the sensitivity of four Mediterranean perennial grasses to O3 and temperature based on plant growth, gas exchange parameters (photosynthesis—A, stomatal conductance—gs, and water use efficiency—WUE), and foliar macro- (N, K, Ca, Mg, P, and S) and micronutrients (B, Cu, Fe, Mn, Mo, and Zn) content. The selected species were grasses inhabiting different Mediterranean habitats from mountain-top to semi-arid grasslands. Plants were exposed to four O3 treatments in Open-Top chambers, ranging from preindustrial to above ambient levels, representing predicted future levels. Chamber-less plots were considered to study the effect of temperature increase. Despite the general tolerance of the grasses to O3 and temperature in terms of biomass growth, WUE and foliar nutrient composition were the most affected parameters. The grass species studied showed some degree of similarity in their response to temperature, more related with phylogeny than to their tolerance to drought. In some species, O3 or temperature stress resulted in low A or WUE, which can potentially hinder plant tolerance to climate change. The relationship between O3 and temperature effects on foliar nutrient composition and plant responses in terms of vegetative growth, A, gs, and WUE constitute a complex web of interactions that merits further study. In conclusion, both O3 and temperature might be modifying the adaptation capacity of Mediterranean perennial grass species to the global change. Air pollution should be considered among the driving factors of biodiversity changes in Mediterranean grassland habitats.
Keywords: Agrostis castellana; Festuca iberica; Festuca indigesta subsp. curvifolia; Stipa tenacissima; gas exchange; plant growth; plant nutrients; O3-sensitivity; climate warming